Analisis Komprehensif Pasal 2 KUHP Nasional: Konsep Hukum yang Hidup dalam Masyarakat, Tantangan Implementasi, dan Implikasi terhadap Asas Legalitas Pidana Indonesia - Sangkala, Robert; Komala, Ida; Wibowo, Satria Ari; Roif, Roif; Asari, Ali; Candra, Firman Adi (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
The enactment of the National Criminal Code (KUHP Nasional) through Law No. 1 of 2023, effective from January 2, 2026, marks a paradigm shift in Indonesian criminal law by introducing Article 2, which recognizes "living law" (hukum yang hidup dalam masyarakat) as a supplementary source of criminal liability. This study employs a normative legal research approach to analyze the philosophical foundations, juridical construction, and practical challenges of Article 2 in balancing material legality with formal legality principles. Two key research problems are addressed: (1) the alignment of living law with the legality principle (nullum crimen, nulla poena sine praevia lege poenali), and (2) implementation challenges in diverse Indonesian contexts. Findings reveal that while Article 2 promotes restorative justice and cultural pluralism aligned with Pancasila, it risks interpretive ambiguity and potential violations of human rights standards. Recommendations include regulatory harmonization and judicial training. This research contributes to the discourse on modernizing Indonesia's pluralistic criminal justice system.